Moringa oleifera Leaf Extract-Mediated Green Synthesis of Nanostructured Alkaline Earth Oxide (MgO) and Its Physicochemical Properties - Archana Venkatachalam; Joseph Prince Jesuraj; kalainathan Sivaperuman (Journal of Chemistry)
The magnesium oxide nanoparticles (MgO NPs) were prepared from Moringa oleifera leaf extract. Phytochemicals are derived from plant extract which are served as stabilizing and capping agents. This green route has been attracted owing to speed, reliable, and eco-friendly and cost-effective one. The synthesized magnesium oxide nanoparticles were taken into three different calcination temperatures (500, 600, and 700°C). The powder X-ray diffraction (PXRD) study shows a pure phase of face-centered cubic structure. Periclase MgO nanoparticles were prepared. The optical band gap of MgO nanoparticles is 4.5 eV, and its absorption in the UV region was observed by UV-visible spectroscopy (UV-Vis). Photoluminescence spectra have exhibited multicolor emissions were being at UV and visible region due to defect centers (F centers) of MgO nanoparticles. EDX (energy dispersive X-ray spectrum) has given the stoichiometric ratio of Mg and O. The functional groups have been studied by Fourier transformed infrared spectroscopy (FTIR), surface morphology transformation has been identified by scanning electron microscopy (SEM) studies, and VSM measurements have given the information of diamagnetic nature of MgO nanoparticles. H-R TEM micrographs have confirmed that particles were in nanorange matched with XRD report. Polycrystalline nature has been observed pattern information. TG-DSC characterization revealed phase transition and weight loss information. D-band and G-band of MgO nanoparticles are studied by micro-Raman analysis. Dielectric analysis has proven that MgO nanoparticles will be a promising candidate for linear dielectric ceramics, thermistor. The present resent studies have revealed that MgO powder will be an economical and promising candidate in superconductor, optoelectronic device, and energy storage applications.